The Problems on English Writing 1 Course: Paragraph: (A Case Study on 1st semester students of English Education program, Universitas Muslim Maros) - Novalia Tanasy; Nashruddin Nashruddin (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2020)
Writing is a skill that requires students to keep on practice. This research is held to answer research questions as follow: (1) What are the writing problems that common appear to the 1st semester students of English Education program of Universitas Muslim Maros in the academic year 2020-2021, and (2) What are the possible factors which cause those students’ problems in writing. This research was conducted in qualitative way. Since this research was conducted during pandemic of Corona Virus 19, Google Classroom application was also used as an instrument. The participants’ selection is based on non-probability sampling based on their availability, time flexibility, convenient and represent some characteristics to ease the writer’s investigation. The writer then analyzed the results of the observation and the interview descriptively. Results of this research showed that (1) most of the students were facing difficulties in Word Chosen, then (2) the main error the students mostly made especially on Grammatical related to connectors, pronoun references and correct verb, (3) whereas on Mechanical the students made mistakes on punctuation, spelling and capitalization. To another research question, this research revealed factors which contributed problems to the students in writing are lack of practice, time distribution and less motivated. Keywords: Writing Skill, Writing Problems, Pandemic Corona Virus